Gastric Tuberculosis Masquerading as Persistent Epigastric Pain in an Immunocompetent Patient: A Case Report - Hasan Al-Obaidi MD; Ahmed Dheyaa Al-Obaidi MBChB; Pratiksha Moliya MD; Hussein Harb MD; Iya Agha MD; Nooraldin Merza MD; Hashim Talib Hashim MD; Mustafa Najah Al-Obaidi MBChB; Osamah Al-Obaidi FIBMS (SAGE Publishing, 2024)
Tuberculosis (TB), caused by Mycobacterium tuberculosis , is a leading infectious disease with varied manifestations. We report a rare presentation of gastric TB in a 50-year-old immunocompetent woman from the Middle East with no prior medical history. The patient presented with persistent epigastric pain, weight loss, nausea, and vomiting over a 2-month duration. Imaging studies and an infectious disease panel were inconclusive. However, upper endoscopy revealed a subepithelial lesion at the pylorus, with biopsies demonstrating caseating granuloma and multinucleated giant cells. A QuantiFERON test was subsequently positive for TB. The patient was successfully treated with standard TB quadruple therapy, resulting in significant improvement in symptoms during follow-up. This case underscores the importance of considering extrapulmonary TB in immunocompetent patients with atypical gastrointestinal symptoms and highlights the efficacy of prompt antitubercular therapy.